Space studies education at the Turkish Air Force Academy - (:unkn) unknown (My University, 2005)
The paper describes the experience in the development of the Space Studies Program at the graduate school of the Turkish Air Force Academy. The graduate school opened in August of 2001, and the space studies program started in August of 2003. Development of the program reported in this paper originates from an expression of the manpower needs of the country in a wide range space related expertise. The paper includes a discussion of the objectives, analysis of the requirements and available capabilities, survey of similar institutions in Turkey and the World, and a description of the curriculum.